Ectopic Hidradenoma Papilliferum - Aristóteles David Neiva Rosmaninho; Maria Teresa Duarte Pinto de Almeida; Vírgilio Costa; Maria Madalena Vasconcelos Sanches; Carlos Lopes; Maria Manuela Selores Gomes Meirinhos (Dermatology Research and Practice)
Hidradenoma papilliferum is a rare tumor that occurs almost exclusively in females on the anogenital area. Rare cases of ectopic (nongenital) hidradenoma papilliferum have been described. The lesions usually present as an asymptomatic slow-growing, red, firm, mobile, well-delimitated nodule that grows for a long time before resection. We describe a case of an 26-year-old man that presented with an enlarging nodule on his right eyelid. The histological findings revealed a hidradenoma papilliferum. So far, among the very few reports of ectopic hidradenoma papilliferum, only a very small number were localized to the eyelid.